232k views
4 votes
What is the answer? I can't figure it out.

What is the answer? I can't figure it out.-example-1
User Jordumus
by
5.4k points

2 Answers

5 votes

√(2z - 6) - √(z + 6) = 0


√(2z - 6) = √(z + 6)


(√(2z - 6))^2 = (√(z + 6))^2


2z - 6 = z + 6


z - 6 = 6


z = 12

Since we squared both sides, we must check the solution on the original equation.


√(2(12) - 6) - √(12 + 6) = 0


√(24 - 6) - √(18) = 0


√(18) - √(18) = 0


0 = 0

Since the solution makes for a true statement, z = 12 is the solution.

Answer: D. z = 12
User Tim Pigden
by
5.6k points
5 votes
rearranging:-)
sqrt(2z - 6) = sqrt(z + 6
squaring both sides
2z - 6 = z + 6
2z - z = 6 + 6
z = 12 (answer)
User Vasiliy Sharapov
by
5.8k points